Reports of equitonic scale systems in African musical traditions and their implications for cognitive models of pitch organization. (December 2019) - Ross, Barry; Knight, Sarah
Psychological research into musical behavior has mostly focused on Western music, explored with experiments utilizing Western participants. This ethnocentric bias limits the generalizability of many claims in the field. We argue that our current understanding of the cognition of pitch organization might be helpfully informed by data gathered in non-Western contexts. In particular, musical traditions featuring equal-spaced scales (where all scale-step interval sizes are equal) are suggested to pose a challenge to popular models of pitch organization, in which unequally spaced scales are suggested to provide cognitive anchor points for on-the-fly pitch orientation. This article presents a summary and theoretical consideration of all available evidence on equal-spaced scales, the vast majority of which appear in east Africa. It is noted that despite equal spacing, there is evidence to suggest that tonal centers are still perceived by idiomatic listeners. We then proceed to propose how such tonal center perception is possible within equal-spaced tonal environments. In short, the existence of equal-spaced scale systems shifts the focus of research from interval uniqueness to alternative explanations for the perception of tonal centers, such as implicit statistical tracking, secondary parameters, recognition of learnt patterns as tonal cues, and so on. Throughout, we note that interdisciplinary work involving ethnomusicologists and psychologists would be beneficial in answering questions about music cognition, and by extension, human cognition in general.